1990
DOI: 10.1111/j.1464-5491.1990.tb01499.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Glycosylated Fibrinogen, Albumin, and Haemoglobin as Indices of Blood Glucose Control in Diabetic Patients

Abstract: The value of glycosylated fibrinogen as an index of short-term diabetic control was compared with indices of long-term (glycosylated haemoglobin) and intermediate-term (glycosylated albumin) diabetic control, respectively. In this study, percentages of these glycosylated proteins and fasting plasma glucose concentration were determined in 95 healthy non-diabetic subjects and 48 diabetic patients (22 well-controlled and 26 poorly-controlled) after an overnight fast. The differences in the percentages of glycosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…One plausible explanation behind the observed dose-dependent effect of aspirin on fibrin network permeability in diabetes is increased glycation of fibrinogen molecules in plasma (13,14). It has been suggested that glycated fibrinogen may have reduced susceptibility to acetylation by aspirin, and competition between glycation and acetylation of fibrinogen amino groups has been observed in vitro (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One plausible explanation behind the observed dose-dependent effect of aspirin on fibrin network permeability in diabetes is increased glycation of fibrinogen molecules in plasma (13,14). It has been suggested that glycated fibrinogen may have reduced susceptibility to acetylation by aspirin, and competition between glycation and acetylation of fibrinogen amino groups has been observed in vitro (23).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we have shown that patients with type 1 diabetes have reduced fibrin network permeability and that improved metabolic control is associated with increased fibrin network permeability (11,12). The altered fibrin network in patients with type 1 diabetes may in part be attributed to increased fibrinogen glycation, as shown in studies on fibrinogen purified from diabetic patients (13,14). Treatment with aspirin increases fibrin network permeability in nondiabetic subjects, possibly through acetylation of lysine residues on plasma fibrinogen (15–17).…”
mentioning
confidence: 93%
“…Glycated fibrinogen has been suggested as a predictor of glycaemic control [28], [29], [30] and [35]. Due to its short half life, glycated fibrinogen is an ideal marker for monitoring short term glycaemic control and therefore the early assessment of the effectiveness of a treatment regime or a research study with a short duration.…”
Section: Discussionmentioning
confidence: 99%
“…openUP Fibrinogen has been shown to be an independent risk marker for CVD [11]. Fibrinogen may contribute significantly to the increased CVD risk in patients with diabetes both in that they generally have elevated fibrinogen levels and that fibrinogen undergoes nonenzymatic glycation in the presence of uncontrolled blood glucose levels in the diabetic subject [12], [13], [14] and [15]. This glycation can alter fibrinogen structure/function, which may then result in the formation of a tight and rigid fibrin network that is resistant to lysis [16], [17] and [18].…”
Section: Referencesmentioning
confidence: 99%
“…Fibrinogen glycation in subjects with diabetes is modulated by improving glycaemic control [76, 78, 82]. Pieters et al observed that improving glycaemia had no effect on the structure of fibrin clots made from T2DM plasma although an effect on clots made from purified fibrinogen was observed [80, 83].…”
Section: Mechanisms Of Hypofibrinolysismentioning
confidence: 99%